Impacts of human disturbance in tropical dry forests increase with soil moisture stress. (21st June 2017) - Chaturvedi, R. K.; Raghubanshi, A. S.; Tomlinson, K.W.; Singh, J. S.
Abstract: Questions: (1) Which disturbances (harvesting, browsing, drought and fire) are important for tree mortality in a tropical dry forest (TDF), and do these change with size class (juvenile, sapling, adult)? (2) How is mortality and recruitment in a TDF related to soil moisture content (SMC) and does the relationship change for different size classes? (3) Is disturbance‐related mortality selectively removing particular species from the TDF? Location: Sonebhadra and Mirzapur districts, Uttar Pradesh, India. Methods: We analysed the structure of a TDF in central India in terms of the tree composition of juveniles, saplings and adults at five distinct sites located along a gradient of SMC, and recorded the numbers of individuals in each size class killed by the four disturbance types over 2 yr. We also recorded total stem density and recruitment at each site. We compared annual mortality index (AMI) and its four disturbance components (harvesting, browsing, drought and fire) and annual recruitment index (ARI) against the mean SMC of each site using GLMM. Results: The impact of all disturbances on total AMI decreased as SMC increased whereas ARI increased as SMC increased. Mortality due to harvesting was substantially higher than other disturbances for adult and sapling trees, whereas both harvesting and browsing were important drivers of mortality for juveniles. There was little evidence that particular species were being deliberately selected for harvesting across sites. Conclusions: Tree saplings and adults in this TDF were mainly killed by harvesting, indicating that anthropogenic impacts on tree mortality are more important than non‐anthropogenic impacts in the TDF, and impacts of all disturbances become more severe with increasing water stress. Thus changes in TDF structure due to harvesting are likely to be more rapid in more arid environments. Abstract : Tree saplings and adults in our study sites in tropical dry forest (TDF) were mainly killed by harvesting, indicating that anthropogenic impacts on tree mortality are more important than non‐anthropogenic impacts, and impacts of all disturbances are more severe with increasing water stress. Thus, changes in TDF structure due to harvesting are likely to be more rapid in more arid environments.